(untitled) (Orfeu, 2017)
Memorial and score of Recordando o Passado by Aldo Krieger for seven-string guitar, premiered at the 4ª Semana Aldo Krieger in July 2016. The arrangement was created using as reference a recording and a book of scores with works of the composer, aiming at preserving the original melody and exploring features and idiomatic effects of the instrument.